IOT and analytics in renewable energy systems AI, ML and IoT; Volume 2 - Swathika, O. V. Gnana; Karthikeyan, K.; Sanjeevikumar, Padmanaban 1978- (CRC Press, 2023)
Smart cities emanate from a smart renewable-energy-aided power grid. The smart grid technologies offer an array of benefits like reliability, availability, and resiliency. Smart grids phenomenally contribute to facilitating cities reaching those sustainability goals over time. Digital technologies, such as the Internet of Things (IoT), automation, artificial intelligence (AI) and machine learning (ML) significantly contribute to the two-way communication between utilities and customers in smart cities. Fivesalient features of this book are as follows: Smart grid to the smart customer Intelligent computing for smart grid applications Novel designs of IoT systems such as smart healthcare, smart transportation, smart home, smart agriculture, smart manufacturing, smart grid, smart education, smart government, smart traffic management systems Innovations in using IoT and AI in improving resilience of smart energy infrastructure Challenges and future research directions of smart city applications
Keywords: Smart power grids; Electric power systems -- Data processing; Internet of things; Renewable energy sources; Réseaux électriques intelligents; Réseaux électriques (Énergie); Informatique; Internet des objets; Énergies renouvelables; Electric power systems; Data processing